2007
DOI: 10.1243/09544119jeim137
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical analysis of ultra-high molecular weight polyethylene-metal hip prostheses

Abstract: In order to predict the frictional heating and the contact stresses between the polyethylene cup and the metallic ball-head forming the articulation of a hip prosthesis a three-dimensional finite element model was developed and calculated. The non-linear model includes a fully coupled thermomechanical formulation of the mechanical properties of the ultra-high-molecular-weight polyethylene, and a large-sliding Coulomb frictional contact between the two components. The model predicts the temperature of the polye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…Depending on the implant type and articulating materials, this increase was observed up to 7°C for a rotating hinge implant (CoCrMo - UHMWPE). In an analytical study, validated by simulator data, temperatures up to 51°C were found in CoCrMo - UHMWPE hip implants [16].…”
Section: Introductionmentioning
confidence: 95%
“…Depending on the implant type and articulating materials, this increase was observed up to 7°C for a rotating hinge implant (CoCrMo - UHMWPE). In an analytical study, validated by simulator data, temperatures up to 51°C were found in CoCrMo - UHMWPE hip implants [16].…”
Section: Introductionmentioning
confidence: 95%
“…Several research activities in the biotribology field are carried out at the Rizzoli Orthopaedic Institute in Bologna in collaboration with the University of Bologna. Different materials and geometries are experimentally tested using commercial joint simulators such as a 12-station hip joint simulator [92][93][94][95][96][97][98][99], a four-station knee joint simulator [100,101], and a three-station knee simulator [102]. Tests are usually run for some million cycles.…”
Section: Biotribologymentioning
confidence: 99%
“…Various roughness parameters were examined in relation to weight losses in reference [94] and skewness seems to give the best correlation. A thermomechanical analysis was also performed using finite-element model to predict the frictional heating and the contact stresses in a polyethylene-metal hip prosthesis [96].…”
Section: Biotribologymentioning
confidence: 99%
“…Therefore, the contact mechanics of different types of THRs have been investigated by many researchers. Jin et al [12], Rocchi et al [13] and Wang et al [14] studied the contact mechanics of the UHMWPE acetabular cup, against a metallic or ceramic femoral head. Quesada et al [15] and Udofia et al [16] investigated the contact mechanics of MOM hipresurfacing prostheses.…”
Section: Introductionmentioning
confidence: 99%